Damage Diagnosis of Drill Bit while Drilling using Wavelet Transform Analysis - Jang, Hyong Doo (Korean Society of Explosives and Blasting Engineering, 2020)
Bit damage is one of the primary causes of decreasing drilling efficacy. Nevertheless the management of bit ware and failure are often left for field engineers' experience. Thus it is imperative to establish a proper system to predict and manage the bit damage during the rock drilling process. In this study, the drilling sound signal has been recorded and analyzed using wavelet transform analysis to identify the exact moment of bit failure. Through the analysis wavelet time-frequency spectrums have been constructed and an abnormal point has been identified with 0.9 of wavelet transform value at the 652.8s on a frequency band around 500Hz. Furthermore it is also observed that the penetration rate of the damaged bit has been decreased to 23mm/s which is 9mm/sec lower than the average of undamaged bit. The study verifies that wavelet transform analysis can be used to build a system to diagnose the bit damage while drilling.